ORTHOPAEDIC RESIDENCY'S HIDDEN CONFLICT: A DETAILED STUDY ON BULLYING - Thompson, James Robert; Walter, Elizabeth Anne (International Research Journal Diagnostics, 2024)
Orthopaedic surgery residents operate within an inherently high-stress environment, contending with a multitude of demands ranging from clinical duties and surgical responsibilities to on-call commitments, educational obligations, research mandates, and life outside the workplace. Unfortunately, the pressure cooker of orthopaedic residency has given rise to alarming rates of burnout, with approximately 42.5% of residents affected. Moreover, the specter of burnout extends its reach, casting a shadow on orthopaedic surgeons, where prevalence rates range from 28.4% to 85.1%.Bullying, a distressing form of mistreatment, remains pervasive in contemporary society. The Centers for Disease Control and Prevention (CDC) and the US Department of Education define bullying as unwelcome or aggressive behaviors that exert a perceived power imbalance, capable of causing harm or distress to the victim. When transplanted into the workplace, bullying manifests as negative actions designed to inflict distress, including the delegation of menial tasks, reduction of responsibilities, deliberate sabotage, information withholding, and unfair criticism. The consequences of workplace bullying are profound, yielding reduced performance, increased workplace errors, and strained interpersonal relationships. Regrettably, bullying's insidious presence is palpable in graduate medical education, as a recent cross-sectional survey exposed a disheartening 48% prevalence across all types of medical residents.